Employment and Career Progression of BEED Graduates of Community Colleges in the Province of Albay, 2018-2021 - Azueta, Leslie; Nasser, Theresa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the employment and career progression of Bachelor of Elementary Education (BEED) graduates from community colleges in the Province of Albay, specifically batches 2018–2021. Anchored on Human Capital Theory, Bandura’s Social Learning Theory, John Dewey’s Theory on Progressive Education, and the proposed L.A. theory of professional motivation, the study used a descriptive-correlational research design through a descriptive survey method. Data were gathered from 456 graduates across selected community colleges in Albay using a validated self-administered questionnaire distributed in printed and online formats. The instrument covered employment status and career progression indicators, while frequency, ranking, weighted mean, and Spearman rank correlation were used in data analysis. The findings showed that most respondents were employed full-time, with many working as elementary school teachers and largely concentrated in the education sector, although a considerable number were also employed in non-teaching or lower-paying positions. Career progression was generally rated positively in terms of career advancement, professional training, leadership roles, and rewards and recognition. However, the study found no significant relationship between employment status and career progression scheme. Key influencing factors included LET eligibility, salary and benefits, access to continuing education or graduate study, teaching practicum experience, personal motivation, and support systems. The study concluded that while BEED graduates were generally employable and showed positive career progression, institutional support remains necessary to strengthen long-term professional growth and employment quality. It recommended stronger career planning, expanded training access, enhanced job placement support, clearer promotion pathways, and stronger institutional linkages. The study aligns with SDG 4 on Quality Education, SDG 8 on Decent Work and Economic Growth, and indirectly with SDG 17 on Partnerships for the Goals. Its sustainability impact lies in supporting educational, institutional, community, and socio-economic sustainability through evidence-based improvement of teacher education programs and graduate support systems.